Wetland conversion to farmland in Bure and Womberma Woredas, Northwestern Ethiopia: Implications for sustainable land use - Belachew Getnet Eneyew; Workiyie Worie Assefa (PLoS ONE, 2026)
This study investigates the reasons why wetlands transformed to farmland. The data were garnered using Landsat, questionnaire surveys, and key informant interviews. Descriptive statistics were applied to analyze LULC change and the perceptions of wetland ecosystem services and attitudes towards wetland cultivation. An ordered probit model was applied to examine the influence of household and experts’ attributes on their attitudes towards wetland cultivation. The findings indicated that despite acknowledging the direct and indirect benefits of wetlands, the majority of households and experts/ department heads have preferred transforming wetlands into farmland. Household age, asset holding size (land and livestock) and livelihood strategies (crop farming and non-farm) as well as the institutional perspectives of experts and department heads have significantly influenced the desire to convert wetlands into agricultural land. Driven by the rising young households’ interest and local governments’ goal to create jobs have led to the distribution of wetlands to unemployed graduates and landless households. Consequently, significant (48%) areas of the wetlands have been transformed into farmlands over the past 36 years. It was found that the environmental soundness of wetlands cultivation has not been considered when converting them into farmland. Efforts should be exerted to expand employment opportunities to minimize the heavy reliance of rural people on wetland farming. Besides, it is imperative to execute agro-ecological evaluation prior to converting wetlands into farmland to ensure farming decisions are environmentally responsible.